Conceptual Project of a Servo-Controlled Power-Assisted Wheelchair - Medola, Fausto O. [UNESP]; Purquerio, Benedito M.; Elui, Valeria M. C.; Fortulan, Carlos A.; IEEE (Ieee, 2014)
Manual and powered wheelchairs have been widely used as assistive technologies to improve users' mobility. However, both types of wheelchairs have problems that limit the users' ability in moving independently, thus impacting social participation, health and quality of life. This paper report on the conceptual development of a manual wheelchair equipped with a servo-controlled power-assisted system. The development process comprised the design of a wheelchair frame properly designed to receive the components of the power-assistance system; the measurement and integrated processing (with an onboard computer) of the user's forces applied to the handrim and rear wheels angular velocity. The integrated processing of these data generates an order to the motor driver, according to an algorithm of conditions that specifies the state (activation or deactivation) and magnitude of operation of the servo-motor. The output torque of the servomotor (located below the seat and between the rear wheels) is distributed to both rear wheels via mechanical differential, thus allowing similar drivability to a standard manual wheelchair. The implementation of the innovative and ergonomic characteristics of the servo-controlled power-assisted wheelchair may improve users' ability to move longer and with comfort and safety, thus benefiting social participation and quality of life.